Household Drinking Water Quality Surveillance In The Working Area of Abeli Community Health Center, Kendari City - Alfiandi; Iyan Megawati Adiwijaya; Suriani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Safe drinking water is a basic human need that must be ensured through continuous quality monitoring. Objective: The purpose of this study is to provide a comprehensive overview of household drinking water quality conditions in the working area of Abeli Community Health Center, Kendari City, in 2024, by reviewing test results based on physical, chemical, and microbiological parameters. Methods: The method used was descriptive, with secondary data analysis obtained from environmental health program reports and the Abeli Health Center profile. Results: Physical examination results showed that all samples met health requirements, although three samples did not meet the color standard. Chemical tests found several parameters that did not comply with Ministry of Health standards, including nitrate, nitrite, chromium, iron, manganese, aluminum, fluoride, and residual chlorine. In terms of microbiology, only one out of fifteen samples met the health quality standard, while most others were contaminated with E. coli and coliform bacteria. Conclusion: The water condition in the working area of Abeli Community Health Center indicates that household drinking water quality remains low and may pose public health risks. Therefore, continuous drinking water quality surveillance, community education, and local government policy support are needed to ensure the provision of safe and consumable household drinking water. Keywords: Drinking water quality, Public Health, surveillance, environmental health, Abeli Community Health Center